2011
DOI: 10.1016/j.jmaa.2011.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Graphs and Gromov hyperbolicity of non-constant negatively curved surfaces

Abstract: In this paper we obtain the equivalence of the Gromov hyperbolicity between an extensive class of complete Riemannian surfaces with pinched negative curvature and certain kind of simple graphs, whose edges have length 1, constructed following an easy triangular design of geodesics in the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 28 publications
(38 reference statements)
0
33
0
Order By: Relevance
“…(see, for example, [6][7][8][9]14,[18][19][20][21][25][26][27][28][29][30][31][32][33][34][35]). x, y ∈ J(G) \ V(G), z ∈ J(G), …”
Section: Introductionmentioning
confidence: 99%
“…(see, for example, [6][7][8][9]14,[18][19][20][21][25][26][27][28][29][30][31][32][33][34][35]). x, y ∈ J(G) \ V(G), z ∈ J(G), …”
Section: Introductionmentioning
confidence: 99%
“…In [5], the equivalence of the hyperbolicity of graphs and negatively curved surfaces was proved. The study of hyperbolic graphs is a topic of increasing interest (see, e.g., and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The study of mathematical properties of Gromov hyperbolic spaces and its applications is a topic of recent and increasing interest in graph theory; see, for instance [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In [25,Section 1.3] is observed that the hyperbolicity of a geodesic metric space is equivalent to the hyperbolicity of a graph related to it (see also [14,16,17]). Hence, establishing hyperbolicity criteria for graphs will be of interest to us.…”
Section: Introductionmentioning
confidence: 99%